Endonuclease IV recognizes single base mismatch on the eighth base 3′ to the abasic site in DNA strands for ultra-selective and sensitive mutant-type DNA detection. Issue 48 (30th July 2018) - Xu, Jiaju; Fu, Yanqiao; Xiao, Yan
Abstract : Endonuclease IV discriminates single basic mismatch in +8 position towards abasic site, which enables the detection of mutations in abundance of 0.01%. Abstract : Since single nucleotide polymorphism (SNP) is related with many diseases and drug metabolic polymorphous and SNP genotyping is rising rapidly in many biological and medical areas, various methods of discriminating SNPs have been developed, one of which is an enzyme-based method. We uncovered a unique property of endonuclease IV due to which it can discriminate single base mismatches in different positions of DNA strands containing an abasic site, and we also discovered a new property: a mismatch in the +8 position could inhibit the cleavage of endonuclease IV. Then, we coupled +8 mismatch with other mismatches along with the discrimination effect of melting temperature to develop a new ultra-selective and sensitive genotyping system, which showed high discrimination factors. The detection limit was as low as 0.05–0.01%. Our new discovery improves the understanding of endonuclease IV. Also, the method could be applied to clinical real samples; thus, it merits further investigation and improvement for application in clinical utilization for early screening of specific diseases.